Manajemen Pelatihan Pengantar Kerja di Pusdiklat Pegawai Kementerian Ketenagakerjaan - Rora Irna Hasanah; Matin Matin; Amril Muhammad (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This study aims to determine the introductory training management at Ministry ofManpower Training and Education Center. In research on training management trainingfocused on the planning and implementation of training. This research is a qualitativedescriptive study. Determining the subject of this study using snowball sampling. Datacollection techniques used were interviews, observation and documentation. Data wereanalyzed by descriptive qualitative.The results of the study indicate that the introductorytraining management Employees working in the Ministry of Employment Training Centerinclude: 1) Planning training in with AKD (Training Needs Analysis) tailored to theneeds on the ground. Formulate the curriculum, syllabus, teaching materials, methods,schedules, and lecturer. After conducting a needs analysis phase, 2) The training beginswith a letter calling the membership then process the results of field organizersformulation of curriculum, syllabus and schedule to be processed into a tentativeschedule. Next is a learning process begins with classical training and learning outsidethe classroom there are street vendors (Practice Field work) in order to train theparticipants in terms of skills. After the stage of the learning process of the next stage isthe end of the training seminar is the last stage of determining graduation trainingparticipants were announced at the closing. Then follow-up after the participants followthe training is coaching and empowerment of the participants returned to the horse'smouth each work unit. Employee Training Center and related Technical Unit shouldprepare earlier and more intensively communicate in detail in preparing the training. theneed for alternative plans or concepts implementation and submitted directly to therelevant parties prior to the implementation of the training in order to anticipate atechnical error or adjustment situation and conditions on the ground so it does not needto re-coordination.